The Artist’s Museum as Reversed Cultural Space - Mark Rectanus (Museum & Society)
During 2019-20, visitors to the Haus der Kunst (HDK), a non-collecting museum for contemporary art in Munich, could view Black Chapel, created by the Chicago-based artist Theaster Gates. Black Chapel was a platform for Gates’s ‘museum within a museum’, or an artist’s museum, composed of Gates’s sculptures, collections of images, and artefacts, including Jesse Owens’s music album collection. This article examines how Gates’s project deploys the historical signifiers and artefacts of Black urban experience in order to challenge the historical space of the Haus der Kunst. I argue that Black Chapel not only contributes to artistic experiments in museum making, it also creates a reversed cultural space and counternarratives within the architectural space of the HDK - a museum which was originally commissioned by Adolf Hitler as a platform for National Socialist art and cultural politics.